Dissemination and Transfer of Animal Feed Technology in Kupang Timur Subdistrict, Kupang Regency - Agus Budiarto; Susinggih Wijana; Essa Noer Bhakty Mulia; Anggraeni Dwi Kusumawati; Muhammad Fhikri Yudha Pratama (Journal of Innovation and Applied Technology)
Kupang Timur Subdistrict has high potential for livestock farming, especially with its large cattle population. Recorded by BPS in 2014, the population of large livestock animals especially beef cattle amounted to 14,077 heads. However, during the dry season, there is often a shortage of feed due to limited knowledge and technology among farmers. This program includes dissemination and transfer of technology, as well as provision of agricultural equipment to farmers. The program aims to continue until the end of November, with the goal to leveling up the knowledge of local farmers. Sustainability will continue to be encouraged by assisting potential farmers and agricultural extension officers as supervisors of the sustainability of the innovations that have been provided